Large-scale brain networks and intra-axial tumor surgery: a narrative review of functional mapping techniques, critical needs, and scientific opportunities - Boerger, Timothy F.; Pahapill, Peter; Butts, Alissa M.; Arocho-Quinones, Elsa; Raghavan, Manoj; Krucoff, Max O. (Frontiers in Human Neuroscience, 2023)
In recent years, a paradigm shift in neuroscience and neurosurgery has been occurring from “localizationism,” or the idea that the brain is organized into separately functioning modules, towards “connectomics,” or the idea that interconnected nodes form networks as the underlying substrates of behavior. Accordingly, our understanding of mechanisms of neurological function, dysfunction, and recovery has evolved from anatomical location alone to include connections, disconnections, and potentially reconnections through neuroplastic mechanisms. Brain tumors provide a unique opportunity to probe these large-scale networks with focal and sometimes reversible lesions, allowing neuroscientists the unique opportunity to directly test newly formed hypotheses about underlying brain structural-functional relationships and network properties. Moreover, if a more complete model of neurological dysfunction is to be defined as a “disconnectome,” potential avenues for recovery might be be mapped through a “reconnectome.” Such insight may open the door to novel therapeutic approaches where previous attempts have failed. This review explores relevant historical and modern brain mapping techniques that are being applied to neurosurgical brain tumor practices with the hope of gaining deeper insight into mechanisms of brain dysfunction and recovery along the way.